2016
DOI: 10.1021/acs.langmuir.6b02267
|View full text |Cite
|
Sign up to set email alerts
|

A Method To Measure Protein Unfolding at an Air–Liquid Interface

Abstract: Proteins are surface-active molecules that have a propensity to adsorb to hydrophobic interfaces, such as the air-liquid interface. Surface flow can increase aggregation of adsorbed proteins, which may be an undesirable consequence depending on the application. As changes in protein conformation upon adsorption are thought to induce aggregation, the ability to measure the folded state of proteins at interfaces is of particular interest. However, few techniques currently exist to measure protein conformation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 25 publications
6
66
0
Order By: Relevance
“…Protein adsorption at the solid/water interface has been studied by a number of groups using techniques such as ellipsometry, fluorescence and quartz crystal microbalance. [11][12][13][14][15][16] These reports provide a useful consensus about the typical ranges observed for the amount of protein adsorbed and its physical state, under well-defined surface and solution conditions.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Protein adsorption at the solid/water interface has been studied by a number of groups using techniques such as ellipsometry, fluorescence and quartz crystal microbalance. [11][12][13][14][15][16] These reports provide a useful consensus about the typical ranges observed for the amount of protein adsorbed and its physical state, under well-defined surface and solution conditions.…”
Section: Introductionmentioning
confidence: 89%
“…Although these studies have demonstrated the relevance of adsorption and desorption processes to structural perturbation and solution aggregation, [10][11][12][13][14][15][16] little insight about mAbs within the adsorbed layers have been reported. Neutron reflection (NR) is a powerful tool able to reveal the thickness and composition of multiple adsorbed protein layers.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, water force the hydrophobic group of polyacylated anthocyanins to interact with the hydrophobic surface and the intramolecular copigmentation disrupted. The occurrence of hydrophobic interactions unfolding caused by the hydrophobic surface had been reported in protein [13,14,15,16]. In addition, the presence of headspace in phials or container was reported to accelerating the recombinant fusion protein [17].…”
Section: The Effect Of Headspacementioning
confidence: 93%
“…Five vertical sieve trays were installed inside the column with a tray spacing of 150 mm and the first one at 200 mm from the column bottom. Their structural parameters were the same as those of Zhang et al A gas distributor (1) made of sintered glass with a pore diameter of 100 ± 20 μm was installed at the column bottom. Through the gas distributor, air was bubbled into the foam fractionation column by an air compressor (ACO‐018A, Guangdong Resun Group Co. Ltd., China), and its volumetric flow rate was controlled by an air rotor flowmeter (60–600 ml/min, LZB‐2, Changzhou Shengzhiyuan Instrument Co. Ltd., China).…”
Section: Methodsmentioning
confidence: 99%
“…In foam fractionation of proteins, a certain loss activity is often observed due to structural unfolding of protein molecules induced by the gas–liquid interface . In addition, the lower protein concentration results in a larger activity loss .…”
Section: Introductionmentioning
confidence: 99%